Staff qualification and the quality of tourism-related services in the Nitra region - Grenčíková, Adriana; Vojtovič, Sergej; Gullerová, Monika (Bulletin of Geography. Socio-economic Series, 2013)
The study attempts to justify the importance of the human potential quality, one of the key factors for the development of tourism industry. Moreover, the study attempts to establish a correlation between the human potential quality and the quality of tourism-related services. Next, the study emphasizes that not only geography-related factors, such as natural, historical and cultural sights, climatic and weather conditions getting the attention and interest by tourists, are vital for tourism industry. The human potential quality, including training, qualification and expertise, is important as well. Therefore, the study analyses the human potential quality in tourism industry, and assesses its impact on the service quality related to accommodation, catering, transport, organization and provision of sports, cultural and sightseeing events.